Advanced Data Encryption ​using 2D Materials. Issue 27 (27th May 2021) - Wen, Chao; Li, Xuehua; Zanotti, Tommaso; Puglisi, Francesco Maria; Shi, Yuanyuan; Saiz, Fernan; Antidormi, Aleandro; Roche, Stephan; Zheng, Wenwen; Liang, Xianhu; Hu, Jiaxin; Duhm, Steffen; et al.
Abstract: Advanced data encryption requires the use of true random number generators (TRNGs) to produce unpredictable sequences of bits. TRNG circuits with high degree of randomness and low power consumption may be fabricated by using the random telegraph noise (RTN) current signals produced by polarized metal/insulator/metal (MIM) devices as entropy source. However, the RTN signals produced by MIM devices made of traditional insulators, i.e., transition metal oxides like HfO2 and Al2 O3, are not stable enough due to the formation and lateral expansion of defect clusters, resulting in undesired current fluctuations and the disappearance of the RTN effect. Here, the fabrication of highly stable TRNG circuits with low power consumption, high degree of randomness (even for a long string of 2 24 − 1 bits), and high throughput of 1 Mbit s −1 by using MIM devices made of multilayer hexagonal boron nitride (h‐BN) is shown. Their application is also demonstrated to produce one‐time passwords, which is ideal for the internet‐of‐everything. The superior stability of the h‐BN‐based TRNG is related to the presence of few‐atoms‐wide defects embedded within the layered and crystalline structure of the h‐BN stack, which produces a confinement effect that avoids their lateral expansion and results in stable operation. Abstract : The few‐atoms‐wide and amorphous native defects in multilayer hexagonal boron nitride (h‐BN) synthesized by chemical vapor deposition can drive out‐of‐plane random telegraph noise current signals that are more stable than those traditionally observed in transition metal oxides. The reason is that these defects are confined and completely surrounded by 2D layered and crystalline h‐BN. This allows fabrication of high‐performance true random number generators for advanced data encryption.